The Influence Of Growth Opportunity And Return On Equity (ROE) Toward Company Capital Structure - Hamdan Hamdan (Ilomata International Journal of Tax and Accounting, 2020)
This study aims to determine the effect of growth opportunity and return on equity the capital structure of the automotive sub-sector companies and components listed on the Indonesia Stock Exchange (IDX) in 2014-2018. The sample used in this study is the automotive sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2014-2018. The sampling technique used was purposive sampling method and obtained 8 companies. The data collected is secondary data with the method of documentation through www.idx.com in the form of a company annual report. The analytical tool used for hypothesis testing is SPPS 20. The results of this study are (1) Growth opportunity does not have a significant effect on the company's capital structure. (2) Return on equity has a significant effect on the company's capital structure.